A Facile and Mild Alkylation Protocol of NH-Diphenyl Sulfondiimines - Xu, Zeyu; Su, Shuaisong; Li, Xue; Jia, Tiezheng (Synlett, 2022)
As a promising pharmacophore, sulfondiimines have drawn increasing attention in recent years, but their uptake in medicinal chemistry is jeopardized by the scarcity of related transformations. Herein, we report a facile and mild N-alkylation protocol of NH-diphenyl sulfondiimines with alkyl halides to prepare a myriad of N-alkylated diphenyl sulfondiimines. Owing to air atmosphere, room temperature, as well as mild reaction conditions, this protocol has exhibited great potential in organic synthesis and medicinal chemistry by the late-stage functionalization of natural products.
Keywords: sulfondiimines; alkylation; mild; alkyl bromides; functional group tolerance